The Structure and Function of Oral Poetry Meurukon - Mohammad Harun; Zulfadli A Aziz; Azrul Rizki; Saifuddin Mahmud; Burhansyah Burhansyah (AT-TA'LIM, 2020)
This study aims to describe the structure and function of the oral poetry Meurukon. This research uses a qualitative approach. The source of research data is the text Meurukon edited by Rahman (2010), Harun (2012), text and recording of Meurukon at the 7th Aceh Culture Event (Huda, 2018). The research data are all sequences relating to the structure and function of Meurukon. Data is collected by using the techniques of listening, recording, and reading. The research instrument consisted of handy cam, stationery, and the researchers themselves. Data analysis was conducted through five stages. The stages are carefully and critically reading Meurukon text, sorting data into Meurukon structure and function, analyzing data comprehensively, verifying research results, and concluding research results. The results of the study indicate that the Meurukon structure includes the opening part which consists of greetings and preface. It also includes the content section which consists of discussions on religious issues, especially about bismillah, problems with prayer, water problems, and problems of faith (aqeedah). Then, the structure of Meurokon is the closing that concern on apology and farewell. Last, the Meurukon functions are religious learning, entertainment, and interactive-dialogical learning model.